Implementasi Pembelajaran Daring dan Luring bagi Anak Usia Dini pada Masa Pandemi Covid-19 - Fitri Febri Handayani; Hibana Hibana; Susilo Surahman (STAI Auliaurrasyidin Tembilahan, 2021)
Corona outbreak or covid-19 that has occurred since 2019 impacts on psychology and human behavior, including the education system in Indonesia, that is broader in a long time. Here teachers and students must adapt online and/or offline learning systems to carry out the learning process. This study is to recognize the implementation of those two learning system for early childhood during the Covid-19 pandemic, especially at PAUD As-Shofa Tembilahan Hulu for the A.Y. 2020/2021. The study is a qualitative decriptive. The data were collected through the use of observation, interview, and documentation. Data analysis used a triangulation on the Miles and Hiberman model. The results showed that PAUD As-Shofa Tembilahan Hulu used various approaches in these both learning system, includes: Home Visits, Limited Face-to-face Learning, and Learning from Home.